Assessment of radial torsion using computed tomography in dogs with and without antebrachial limb deformity. Issue 1 (9th December 2016) - Kroner, Kevin; Cooley, Katie; Hoey, Seamus; Hetzel, Scott J.; Bleedorn, Jason A.
Abstract: Objective: To evaluate the reliability of radial torsion assessment in dogs using computed tomography (CT). Study Design: Cadaveric and retrospective observational clinical study. Animals: Thoracic limbs ( n  = 40) from bilateral normal cadaveric canine specimens (10 pairs) and unilateral antebrachial angular limb deformity (ALD) dogs (10 uniapical and 10 biapical deformities). Methods: Limbs were evaluated using CT. Frontal, sagittal, and axial plane (torsion) values were obtained using published guidelines and compared between groups and limbs. Radial torsion reliability was assessed among 3 observers using intraclass correlation coefficients (ICC). Results: The mean (±SD) radial torsion of normal dogs was 3.6° ± 6.4° and contained a significant right to left limb variation of 2.6°. Mean radial torsion in uniapical ALD limbs (3.6° ± 18.7°) was not significantly different from biapical ALD limbs (8.9° ± 17.9°). There was a wide range of torsion values in normal and ALD limbs. The interobserver reliability was excellent (ICC > 0.8) for normal dogs, good (0.73) for uniapical, and excellent (0.89) for biapical ALD limbs. The intraobserver reliability was excellent (>0.8) for all groups. Conclusion: There was a small side‐to‐side variation of radial torsion in normal dogs. With directed training, torsion assessment using CT is reliable in dogs with and without antebrachial bone deformity.